2017
DOI: 10.1073/pnas.1713012114
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon test for demographic events in written and oral history

Abstract: We extend an established simulation-based method to test for significant short-duration (1-2 centuries) demographic events known from one documented historical and one oral historical context. Case study 1 extrapolates population data from the Western historical tradition using historically derived demographic data from the catastrophic European Black Death/bubonic plague (). We find a corresponding statistically significant drop in absolute population using an extended version of a previously published simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 30 publications
(36 reference statements)
0
76
0
Order By: Relevance
“…This was one of the case studies used by Contreras and Meadows (2014) to illustrate the difficulties in identifying such events in radiocarbon data; they concluded that the consequence of the Black Death, a 30% drop in population, is difficult to Bsee^even when randomly sampling calendar dates from the population curve, and virtually impossible when viewed through the heavy fog of the calibration process. However, as Edinborough et al (2017) point out, such demographic events can be positively associated with changes in simulated summed radiocarbon probability distributions by deploying a hypothesis-testing approach-if, of course, there really is a direct link between demography and the production rate of materials destined to become 14 C samples, which is another debate entirely. To test whether the Gaussian KDE can resolve the Black Death Bevent^under a similar set of assumptions, the historic demographic data were used to simulate various numbers of calendar dates whose frequency distribution in time was randomly sampled from the demographic data supplied by Contreras and Meadows (2014) for the period AD 1000 to 1700.…”
Section: Testing the Method: The Black Deathmentioning
confidence: 99%
See 3 more Smart Citations
“…This was one of the case studies used by Contreras and Meadows (2014) to illustrate the difficulties in identifying such events in radiocarbon data; they concluded that the consequence of the Black Death, a 30% drop in population, is difficult to Bsee^even when randomly sampling calendar dates from the population curve, and virtually impossible when viewed through the heavy fog of the calibration process. However, as Edinborough et al (2017) point out, such demographic events can be positively associated with changes in simulated summed radiocarbon probability distributions by deploying a hypothesis-testing approach-if, of course, there really is a direct link between demography and the production rate of materials destined to become 14 C samples, which is another debate entirely. To test whether the Gaussian KDE can resolve the Black Death Bevent^under a similar set of assumptions, the historic demographic data were used to simulate various numbers of calendar dates whose frequency distribution in time was randomly sampled from the demographic data supplied by Contreras and Meadows (2014) for the period AD 1000 to 1700.…”
Section: Testing the Method: The Black Deathmentioning
confidence: 99%
“…Gaining momentum is what Edinborough et al (2017) call the BUniversity College London (UCL) method^, where simulation and back-calibration are used to generate a null hypothesis, which can also factor the expected rates of both population growth and taphonomic loss of archaeological materials through time. Through comparison of summed radiocarbon to the simulated model, signals of activity that are significantly weaker or stronger than usual can be identified.…”
Section: Summed Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade population dynamics and demographic variation in Mesolithic and Neolithic societies have been thoroughly investigated by using summed radiocarbon probability plots as a population proxy (Apel et al, 2017;Edinborough, 2009;Hinz et al, 2012;Shennan et al, 2013;Shennan and Edinborough, 2007;Timpson et al, 2014). The scopes of the studies are impressive and the methods and models applied to investigate demographic variation are becoming increasingly complex (Edinborough et al, 2017: 1-2 for overview of development; Shennan et al, 2013;Timpson et al, 2014). Basically, reconstructions of prehistoric demography are based on temporal distribution of radiocarbon dates, which are used as a proxy of variation in human activity through time.…”
Section: Introductionmentioning
confidence: 99%